If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -3 = 82 Reorder the terms: -3 + 8x = 82 Solving -3 + 8x = 82 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 8x = 82 + 3 Combine like terms: -3 + 3 = 0 0 + 8x = 82 + 3 8x = 82 + 3 Combine like terms: 82 + 3 = 85 8x = 85 Divide each side by '8'. x = 10.625 Simplifying x = 10.625
| -9r=-10r-2 | | 5n-20=4n+24 | | 4f^2-36=0 | | G^2-21=100 | | -12x+21y=1 | | 1-3c=-2c-9 | | -8+5s=6s | | 2a+5=22 | | -5+8p=7p+3 | | 9u^2+81=0 | | 9c+5-2c-3= | | 6t^2-35=19 | | 5/8=6/3 | | -8k=-7k-8 | | 20x+10=4-10x | | 2k^2=0 | | 3t+-14=41 | | 4z^2-94=6 | | -7b=-8b+7 | | 3x+55=14 | | 7/5x-3/20=1/2x | | 3t-(14)=31 | | H^2-12=52 | | 18/27=r/3 | | -3f=-2f-1 | | y=5(1)+2 | | Y^2+42=51 | | 3t-14=31 | | 5m^2-19=26 | | 6w=5w+4 | | 7/k-3/4-5k=3/8 | | 9/10i |